E-Book: Inovasi Media Pembelajaran Digital Muatan Pelajaran IPS Kelas V Sekolah Dasar - Aristiani, Ni Kadek Rita; Anak Agung Gede Agung (Universitas Pendidikan Ganesha, 2022)
The low interest and social studies learning outcomes of fifth-grade students are due to the need for more media use. So that the purpose of this study is to develop an E-Book based on Problem-Based Learning social studies class V elementary school content. This research belongs to the type of development research that was developed using the ADDIE model. The subjects involved in this study were four experts and nine fifth-grade elementary school students. Data collection in the study was carried out using interviews, questionnaires/questions, and tests, with research instruments in the form of questionnaires and multiple-choice tests (objective). The data obtained in this study were then analyzed using quantitative descriptive and inferential statistical analysis techniques. The results of the research analysis showed that the validity test results according to content/subject matter experts scored 91.67% with very good qualifications, instructional design experts scored 88.6% with good qualifications, and learning media experts scored 90% with very good qualifications. The individual trials scored 97.5% with very good qualifications. The small group trials obtained a score of 92.2% with very good qualifications—the effectiveness test results show significant differences before and after using the E-Book. Based on the research analysis results, the learning media in the form of E-Books based on Problem-Based Learning in social studies class V SD is feasible to develop and teach because it can improve student learning outcomes.